STRATEGI PENGENDALIAN PENCEMARAN AIR SUNGAI GUDE PLOSO DI KABUPATEN JOMBANG - Lilik Purwati (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The aims of this research were to analyze the water quality condition of Gude Ploso river with physical (temperature, TSS, TDS), chemical (pH, DO, BOD, COD, Nitrate and Phosphate), and microbiology (coliform total bacteria) indicators; to analyze the water quality status of Gude Ploso river; and to formulate a pollution control strategy in Gude Ploso river water with SWOT analysis. The length of the Gude Ploso river for the experiment location was 5,110 km. River water sampling was conducted at 4 monitoring points (TP1, TP2, TP3, TP4). The sampling was conducted in June 2016. The analysis results found that the water quality condition of the Gude Ploso river has decreased. It was shown by the existence of parameters (temperature, DO, BOD, COD, Phosphate, and coliform total bacteria) in the water, which exceeded the criteria of water quality classification II according to Perda Provinsi Jawa Timur No. 2 year 2008. The temperature parameter was found at the monitoring point 2, the DO and COD parameters were found at the monitoring point 2, 3, and 4, the BOD parameter was found at the monitoring point 1, 2, 3, and 4, the phosphate parameter was found at monitoring point 3 and 4, and the coliform total bacteria parameter was found at the monitoring point 2 and 3. The highest value of BOD, COD, and temperature parameters was at monitoring point 2. Based on water quality status assessment with Pollution Index method, Gude Ploso river’s water quality indicated that there was a decrease in quality from upstream to downstream area, which is categorized as lightly polluted in all the monitoring points based on the criteria of water quality classification II according to Perda Provinsi Jawa Timur No. 2 year 2008.